From Intuition to Computation. Development and problems of medical diagnosis - Gross, R. (Methods of Information in Medicine, 1966)
Modern medical diagnostics are determined by continued influence and mutual interference of 3 essential periods of their development: Empirism and intuition — physical and chemical measurements — computation and other applications of the theory of probabilities.The advantages and disadvantages of each of these methods are discussed regarding the diagnostic task as well as the relation between doctors and patients. Diagnostic processes are compared as performed by the human brain and by computers.In internal medicine the diagnostic difficulties and possibilities have reached some kind of culmination.The great number of system-diseases with their manifestation at so many organs, the rather uniform response of these organs to quite different injuries, corresponding to their structure and function, demonstrate the limits of a to narrow spezialization and a stencil-like automatisation.